Metabarcoding From Microbes to Mammals: Comprehensive Bioassessment on a Global Scale - Compson, Zacchaeus G.; McClenaghan, Beverly; Singer, Gregory A. C.; Fahner, Nicole A.; Hajibabaei, Mehrdad (Frontiers in Ecology and Evolution, 2020)
Global biodiversity loss is unprecedented, and threats to existing biodiversity are growing. Given pervasive global change, a major challenge facing resource managers is a lack of scalable tools to rapidly and consistently measure Earth’s biodiversity. Environmental genomics tools provide some hope in the face of this crisis, and DNA metabarcoding is a powerful approach for biodiversity assessment at large spatial scales. However, metabarcoding studies are variable in their taxonomic, temporal, or spatial scope, investigating individual species, specific taxonomic groups, or targeted communities at local or regional scales. With the advent of modern, ultra high throughput sequencing platforms, conducting deep sequencing metabarcoding surveys with multiple DNA markers will enhance the breadth of biodiversity coverage, enabling comprehensive, rapid bioassessment of all the organisms in a sample. Here, we report on a systematic literature review of 1,563 articles published about DNA metabarcoding and summarize how this approach is rapidly revolutionizing global bioassessment efforts. Specifically, we quantify the stakeholders using DNA metabarcoding, the dominant applications of this technology, and the taxonomic groups assessed in these studies. We show that while DNA metabarcoding has reached global coverage, few studies deliver on its promise of near-comprehensive biodiversity assessment. We then outline how DNA metabarcoding can be a tool for near real-time, global bioassessment, illustrating how different stakeholders could benefit from DNA metabarcoding. Next, we address barriers to widespread adoption of DNA metabarcoding, highlighting the need for standardized sampling protocols, experts and computational resources to handle the deluge of genomic data, and standardized, open-source bioinformatic pipelines. Finally, we explore how technological and scientific advances will realize the promise of total biodiversity assessment in a sample—from microbes to mammals—and unlock the rich information genomics exposes, opening new possibilities for merging whole-system DNA metabarcoding with (1) abundance and biomass quantification, (2) advanced modeling to improve species detection, (3) population genetics, (4) phylogenetics, and (5) food web and functional gene analysis. Concurrent scientific and technological advances will usher in unprecedented environmental genomic approaches that will supplement existing biomonitoring tools reliant on morphological and abiotic data. Collectively, these new approaches will aid in addressing the global biodiversity crisis we now face.